The business cycle’s influence on share repurchases of the UK - Sodhi, Adhiraj; Mateus, Cesario; Mateus, Irina; Stojanovic, Aleksandar (Journal of Economic Analysis, 2023)
The UK fully legalised open market share repurchases in 1981, and to our knowledge no study has investigated the business cycle’s influence on repurchase decision-making. We address this aspect and investigate the period 1985-2014. This is relevant as the business cycle factors impact the firm-specific variables such as cash flow, profitability, dividends and capital structure, and these factors traditionally influence repurchase decisions. This forms the paper’s theoretical intuition, and the empirical objectives test the business cycle’s influence on the decision to undertake a repurchase, and also its influence on repurchases values. The results find that the business cycle influences both the decision of undertaking repurchases and repurchases’ values, and this influence has aggregately remained positively associated with economic prosperity. Thus, the frequency of repurchase announcements by British firms is more probable during prosperous economic circumstances. The results also reveal that the repurchase-business cycle relationship witnessed a structural break in 1996:Q2, and the real difference following this break is the increase in the business cycle’s influence on the decision regarding repurchase values. The paper thus contributes to existing literature by directly testing the UK’s repurchase-business cycle relationship, and providing detailed empirical evidences that business cycle conditions strongly impact the repurchase decision-making.